(untitled) (Research, Society and Development, 2022)
Syphilis, despite all the use of Health Policies to minimize its occurrence, for various reasons, continues to affect pregnant women, newborns, and children. The objective of this work is to report a case of congenital syphilis with late diagnosis in a teaching hospital. It is a disease of easy diagnosis and treatment, with a historical reduction after the discovery of penicillin in the 40’s. However, in the 21st century this pathology has returned to a significant growth, with this, the lack of attention is highlighted. pre- and post-natal care for the screening and diagnosis of the disease. In order to treat the child in advance, many times, even before the symptoms appear. This work seeks to report a case of late diagnosed congenital syphilis, showing the damage caused by the disease and emphasizing the importance of screening, diagnosis, and treatment.